2022
DOI: 10.1002/adfm.202204825
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Hole‐Transport Layer and Interface Passivation on Halide Segregation in Mixed‐Halide Perovskites

Abstract: Mixed-halide perovskites offer ideal bandgaps for tandem solar cells, but photoinduced halide segregation compromises photovoltaic device performance. This study explores the influence of a hole-transport layer, necessary for a full device, by monitoring halide segregation through in situ, concurrent X-ray diffraction and photoluminescence measurements to disentangle compositional and optoelectronic changes. This work demonstrates that top coating FA 0.83 Cs 0.17 Pb(Br 0.4 I 0.6 ) 3 perovskite films with a pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 86 publications
(196 reference statements)
1
15
0
Order By: Relevance
“…Since PL is one of the most widely used and easily accessible techniques to study halide segregation, one should be aware that the direction of a PL shift does not necessarily reflect the halide distribution after segregation, and sometimes it may be misleading due to the carrier-funneling or morphology degradation effects. A similar conclusion was also recognized by Lim et al, who combined PL and in situ X-ray diffraction to study the light-induced halide segregation in the presence of a hole-transport layer and suggested that PL needs to be paired with other techniques that can provide information on the bulk of the samples . Thus, experiments designed to study halide phase separation phenomena in perovskites should consider and account for the complexities enumerated here.…”
supporting
confidence: 76%
See 1 more Smart Citation
“…Since PL is one of the most widely used and easily accessible techniques to study halide segregation, one should be aware that the direction of a PL shift does not necessarily reflect the halide distribution after segregation, and sometimes it may be misleading due to the carrier-funneling or morphology degradation effects. A similar conclusion was also recognized by Lim et al, who combined PL and in situ X-ray diffraction to study the light-induced halide segregation in the presence of a hole-transport layer and suggested that PL needs to be paired with other techniques that can provide information on the bulk of the samples . Thus, experiments designed to study halide phase separation phenomena in perovskites should consider and account for the complexities enumerated here.…”
supporting
confidence: 76%
“…A similar conclusion was also recognized by Lim et al, who combined PL and in situ X-ray diffraction to study the light-induced halide segregation in the presence of a hole-transport layer and suggested that PL needs to be paired with other techniques that can provide information on the bulk of the samples. 47 Thus, experiments designed to study halide phase separation phenomena in perovskites should consider and account for the complexities enumerated here.…”
Section: Brmentioning
confidence: 99%
“…The progress of halide segregation under photoexcitation may be tracked via measurement of the absorption, [33,[61][62][63]76,81] X-ray diffraction (XRD), [61,65,[82][83][84][85] or PL [27,39,41,54,61,62,65,66,76,86,87] spectra. Whereas light absorption and XRD measurements probe the volume average of the mixed-halide perovskite, the PL spectra are dominated by emission from the low-bandgap iodide-rich domains, into which charge carriers funnel.…”
Section: Temperature and Light-intensity Dependence Of Halide Segrega...mentioning
confidence: 99%
“…[27,56,66] While the x = 0.5 composition has been widely investigated in halide-segregation studies, [39,41,61,63,82] mixed halides with x = 0.4 result in a bandgap that is optimal for top cells [88] in perovskite-silicon tandems. [18,30,82,85,88] Mixed-halide perovskites with lower bromide fractions exhibit slower segregation rates, [27,65] aiding the temporal resolution of changes that occur under illumination, while the correlation between their degree of phase segregation and PL intensity is stronger. [65] Here, we study both MAPb(Br 0.4 I 0.6 ) 3 and MAPb(Br 0.5 I 0.5 ) 3 solution-processed thin films, topped with a layer of poly(methyl methacrylate) (PMMA) to exclude atmospheric influence on halide segregation dynamics, [39] prepared as described in the Supporting Information.…”
Section: Temperature and Light-intensity Dependence Of Halide Segrega...mentioning
confidence: 99%
“…Therefore, an in-depth study on how different HTLs affect light-induced halide segregation is necessary for the design of stable mixed-halide perovskite-based optoelectronic devices. So far, only a few reports have looked into the effect of HTLs on light-induced halide segregation; some observe that an HTL can accelerate light-induced halide segregation, , while others report an opposite trend. Notably, only a single HTL material was used in each of those studies, making unambiguous conclusions challenging.…”
Section: Introductionmentioning
confidence: 99%